Implementations of Plant Tissue Culture Technique in Producing Hybrid Plants: (Article Review) - K. Mohammed, Rasha; Hamdi Jassim, Emad; I. Salih, Maha (Al-Nahrain Journal of Science, 2025)
Plant tissue culture methods have greatly improved the process of producing hybrid plants. These techniques, which include callus culture, somatic embryogenesis, Anther and Pollen Culture to Production of Haploid Plants, somatic hybridization by protoplast fusion and Fertilization conducted in a test tube, hairy roots provide reliable means of creating a large number of consistent, superior hybrids. With the use of micropropagation, hybrid plants can be quickly multiplied from a small tissue sample, guaranteeing excellent yield and genetic consistency. The Somatic embryogenesis process aids in the formation of embryos from somatic cells, making the manufacturing of hybrid plantlets scalable and effective. Embryo rescue gets around obstacles to hybridization by promoting the development of embryos from crossings that might not otherwise mature. In order to produce hybrids with desired features, callus culture aids in the regeneration of plants from undifferentiated cell masses. When combined, these methods improve hybrid plant production’s efficiency, homogeneity, and viability while removing historical barriers and raising the bar for creative crop breeding and conservation. This abstract emphasizes the main techniques and advantages of using plant tissue culture to produce hybrid plants, highlighting the significance of this practice for contemporary horticulture and agriculture.